2007
DOI: 10.1042/bj20070983
|View full text |Cite
|
Sign up to set email alerts
|

Human iron regulatory protein 2 is easily cleaved in its specific domain: consequences for the haem binding properties of the protein

Abstract: Mammalian IRPs (iron regulatory proteins), IRP1 and IRP2, are cytosolic RNA-binding proteins that post-transcriptionally control the mRNA of proteins involved in storage, transport, and utilization of iron. In iron-replete cells, IRP2 undergoes degradation by the ubiquitin/proteasome pathway. Binding of haem to a 73aa-Domain (73-amino-acid domain) that is unique in IRP2 has been previously proposed as the initial iron-sensing mechanism. It is shown here that recombinant IRP2 and the 73aa-Domain are sensitive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 42 publications
(57 reference statements)
3
17
1
Order By: Relevance
“…The broad Soret band for the heme bound Irr also corresponds to multiple configurations of heme binding in Irr. Such a broad Soret band was also reported for the HRM containing heme-regulated proteins such as Hap1 (23), Bach1 (24), and IRP2 (12, 25). The ligation of 29 Cys to the heme iron is, therefore, heterogeneous and distinct from the conventional Cys-ligated hemoproteins, which is characteristic for heme-regulated proteins with the HRM.…”
Section: Resultssupporting
confidence: 63%
“…The broad Soret band for the heme bound Irr also corresponds to multiple configurations of heme binding in Irr. Such a broad Soret band was also reported for the HRM containing heme-regulated proteins such as Hap1 (23), Bach1 (24), and IRP2 (12, 25). The ligation of 29 Cys to the heme iron is, therefore, heterogeneous and distinct from the conventional Cys-ligated hemoproteins, which is characteristic for heme-regulated proteins with the HRM.…”
Section: Resultssupporting
confidence: 63%
“…IRP2 binds a Cys-ligated heme in a HRM, and heme binding underpins its iron-sensing mechanism (19). Heme may bind only to a truncated IRP2 that is specifically proteolyzed as part of the regulatory mechanism (20). However, another proposal is that C-terminal cysteines bind iron directly and that heme has no role in IRP2 degradation (21).…”
Section: Iron Heme and Oxidative Stress Responsementioning
confidence: 99%
“…However, a mutant IRP2 protein lacking this 73-amino acid region degraded at a rate similar to that of wild-type IRP2 (106). Dycke et al, (2007) showed this sequence is an active non-iron dependent cleavage domain in cultured breast cancer cells, and that it is unlikely that the iron-dependent degradation of IRP2 is mediated by haem binding to the intact 73 aa domain (107). These results are relevant to AD since oxidative stress is important during AD and the APP mRNA has an active IRE in its 5′UTR (Figure 4).…”
Section: B Ferritin Translational Control: Links To App and Asyn Mrnmentioning
confidence: 99%